Dual Innovation, Financial Slack and Business Performance—Experiential Data from Private Enterprises - Jianfei Zhou (Journal of World Economy, 2023)
Taking the data of 337 private enterprises in Shanghai and Shen Zhen from 2011-2017 as the research sample, constructing the relationship framework of “innovation-performance” based on the regulation effect of financial slack is established, and exploring the relationship between dual innovation and enterprise business performance. The empirical research shows that exploration innovation and development innovation are significantly positively correlated with enterprise performance, and development innovation is more conducive to the improvement of enterprise performance; financial slack plays a negative role in regulating the relationship between exploration innovation and development innovation and enterprise performance.